Intraoperative Evaluation of Dorsal Screw Prominence after Polyaxial Volar Plate Fixation of Distal Radius Fractures Utilizing the Hoya View: A Cadaveric Study. (December 2014) - Dolce, Donald; Goodwin, David; Ludwig, Meryl; Edwards, Scott
Background: The irregular nature of the dorsal surface of the distal radius makes it difficult to detect prominent screws with volar plate fixation for distal radius fractures using standard fluoroscopic images. This study evaluates the accuracy of a new radiographic method, the Hoya view, for the assessment of dorsal cortical screw penetration with volar plate fixation. Methods: Eight cadaveric upper extremities underwent application of a volar distal radius plate with polyaxial locking screws placed distally. Utilizing a mini C-arm, lateral and Hoya views were obtained with notation of any dorsal cortical screw prominence. Dissection of the cadavers was then performed for direct visualization of screw prominence. The screws were then exchanged sequentially for screws 2-mm longer than their initial measurements with repeated imaging and direct visualization. Results: The Hoya view revealed that 9.4 % of the screws penetrated the dorsal cortex with an average screw prominence of 1.08 mm (range 0.5–2 mm). None of the six prominent screws were detected with lateral views. With the Hoya view, six of six prominent screws were identified. With locking screws exchanged for screws 2-mm longer, 76.6 % of the screws had violated the dorsal cortex; of these, 24.5 % were detected with lateral imaging versus 100 % with the Hoya view. Conclusions: This study supports the intraoperative use of the Hoya view to evaluate screw length and dorsal cortical screw penetration in volar plate fixation of distal radius fractures. However, this view may be difficult to obtain in patients with limitations in elbow or shoulder range of motion.